2016
DOI: 10.1093/cvr/cvw080
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular tortuosity underlies slow cAMP diffusion in adult ventricular myocytes

Abstract: Aims3′,5′-Cyclic adenosine monophosphate (cAMP) signals in the heart are often confined to concentration microdomains shaped by cAMP diffusion and enzymatic degradation. While the importance of phosphodiesterases (degradative enzymes) in sculpting cAMP microdomains is well established in cardiomyocytes, less is known about cAMP diffusivity (DcAMP) and factors affecting it. Many earlier studies have reported fast diffusivity, which argues against sharply defined microdomains.Methods and results[cAMP] dynamics i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 48 publications
4
52
0
Order By: Relevance
“…Time delays in calcein fluorescence measured at different distances from the bleaching region provide a readout of cytoplasmic diffusivity (D calc ), measured to be 47.8 ± 5.95 μm 2 /s, i.e. 13-fold lower than in water (~600 μm 2 /s)30 (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Time delays in calcein fluorescence measured at different distances from the bleaching region provide a readout of cytoplasmic diffusivity (D calc ), measured to be 47.8 ± 5.95 μm 2 /s, i.e. 13-fold lower than in water (~600 μm 2 /s)30 (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, our data showed that active SNs function as point-sources of NE, which consistently activate cAMP generation from the corresponding junctional membrane portion. Previously, it was reported that free diffusion of cAMP in the cellular matrix is restricted both through degradation by phosphodiesterases (Jurevicius & Fischmeister, 1996;Perry et al, 2002;Zaccolo & Pozzan, 2002;Mongillo et al, 2004), as well as by physical barriers created by the tortuous CM ultrastructure, including the positioning of mitochondria and sarcomeres (Agarwal et al, 2016;Richards et al, 2016). The obvious implication of confined subcellular cAMP signalling is that rapid and simultaneous cAMP/PKA-dependent effects (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, mathematical models predict that even with slow diffusing cAMP (∼10-35 µm 2 s −1 ) the sole PDE action is not sufficient to generate microdomains (Yang et al, 2016). These data would suggest that the formation of cAMP microdomains is likely to be a multi-parametric phenomenon where more than one mechanism such as enrichment in selected subcellular compartments of different types of adenylyl cyclases (ACs) and effectors, physical barriers (Richards et al, 2016), and cAMP buffering (Agarwal et al, 2016) that limit cAMP diffusion, along with specific localization of PDEs and PKA co-occur to ensure the existence of distinct cAMP events within the cell. Interested readers are referred to a recent review for a more detailed discussion of this topic (Feinstein et al, 2012;Saucerman et al, 2014).…”
Section: Targeting Geis To Organellesmentioning
confidence: 99%